Design of brain imaging agents for positron emission tomography: do large bioconjugates provide an opportunity for in vivo brain imaging?. (September 2013) - Schirrmacher, Ralf; Bernard-Gauthier, Vadim; Reader, Andrew; Soucy, Jean-Paul; Schirrmacher, Esther; Wängler, Björn; Wängler, Carmen
The development of brain imaging agents for positron emission tomography and other in vivo imaging modalities mostly relies on small compounds of low MW as a result of the restricted transport of larger molecules, such as peptides and proteins, across the blood–brain barrier. Besides passive transport, only a few active carrier mechanisms, such as glucose transporters and amino acid transporters, have so far been exploited to mediate the accumulation of imaging probes in the brain. An important question for the future is whether some of the abundant active carrier systems located at the blood–brain barrier can be used to shuttle potential, but non-crossing, imaging agents into the brain. What are the biological and chemical constrictions toward such bioconjugates and is it worthwhile to persue such a delivery strategy?